Channel Coding Diversity with Mismatched Decoding Metrics - Nguyen, T. T.; Lampe, L. (IEEE communications letters, 2011)
We analyze the performance of channel coding diversity with general decoding metrics in terms of the generalized mutual information (GMI). We show that the GMI of the diversity channel is less than or equal to the baud-rate weighted sum of the component GMIs; and equality is achieved only in special cases. We then focus on bit-interleaved coded modulation (BICM) schemes and demonstrate the applicability of our findings by an example of hybrid free-space optical and radio-frequency (FSO-RF) communication.